The importance of plasma paste boriding parameters for thickness, nanomechanical properties, residual stress distribution and fracture toughness of layers produced on Nimonic 80A-alloy. (November 2022) - Dziarski, Piotr; Makuch, Natalia
Graphical abstract: Highlights: compressive residual stresses were generated in the borided layers. increase in the layer thickness resulted in increased fracture toughness. cracks propagation energy was balanced by the formation of a plastic zone. in thin layers the limited propagation of the plastic zones occurred. in thick layers a uniform growth of the plastic zone was possible. Abstract: Borided layers of different thickness were produced on Nimonic 80A-alloy using plasma paste boriding method. The process was carried out at the temperature of 750 °C, 800 °C and 850 °C for 3 h and 6 h. All produced layers consisted of a fine-grained mixture of nickel borides and chromium borides. Higher boriding temperature and time resulted in the obtaining of boron-rich CrB phase in the microstructure of the borided layer. Simultaneously, this layer was characterized by higher hardness and Young's modulus. Compressive residual stresses were generated in all produced layers. However, the most advantage course of the curve is characteristic of the borided layer produced at the highest temperature and time. The increase in layer thickness was accompanied by a decrease in the crack's length (from 33.8 to 7.7 µm), as well as an increase in the fracture toughness (from 0.4439 to 2.4087 MPa·m 1/2 ).